Digital Social Support Does Not Enhance Eudaimonic Well-Being in Fashion Brand e-WOM Communities: Evidence from Three-Year Digital Trace Data - Mohamad Reza Nurpratama; Vanessa Gaffar; Bambang Widjajanta; Lisnawati Lisnawati; Rini Larasati Irawan (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2026)
This study examines whether digital social support (DSS) in fashion brand electronic word-of-mouth (e-WOM) communities influences consumers’ eudaimonic well-being (EWB). Grounded in Self-Determination Theory and Social Support Theory, the study positions meaning orientation (MO) as a mediator and online toxicity (OT) as a moderator. Digital trace data from 400 active consumers comprising 20,134 comments across three platforms (YouTube, Reddit, and X/Twitter) over the period January 2023–December 2025 were analyzed using SEM-PLS (SmartPLS). Results indicate that DSS does not significantly affect EWB either directly or through MO. The moderating effect of online toxicity is also non-significant. These findings suggest that social support within fast fashion consumption spaces does not automatically translate into meaningful psychological well-being. This study contributes by identifying a boundary condition in the digital social support and well-being literature within commercial contexts.